Proposal for the creation of a Center for Learning Resources (CRA) in the School of San Lorenzo de Tarrazu - Valverde Sánchez, Jorge Luis (2011)
This research proposes the creation of a C.R.A for the users of the School of San Lorenzo de Tarrazú. This is because a C.R.A. not only implies a modification in its structural organization and didactic resources; it also implies the development of a new concept of library, conceived as a dynamic and meeting space, in which a great diversity of educational resources is gathered.